Ischemie stroke due to embolie heart diseases and associated factors in Benin hospital setting.. - GNONLONFOUN, DIEU-DONNÉ; ADJIEN, KODJO CONSTANT; GNIMAVO, RONALD; Hotcho, CORINNE; SOWANOU, ARLOS; Gnigone., PUPCHEN; HOUINATO, Dismand (My University, 2018)
In/roductioll-' Poor access to cardiovasculilf checkups is a major cause of ignorance of embolie hean disea.<es as the etiulogy for iscbemic stroke. Objective: Study îschemic strokes due to embolie heart diseases and theîr associated factors. Method: It was a crosscsectional, prospective, des 'ptive and analytieal study eonducted from November 1, 2014 (0 August 31, 2015 on 104 pfItients with ischemie stroke confirmed through brain imaging. Embolie heilrt diseascs induded arrhyrhmia due to atriaJ fibrillation (AF), alTlal f]uttCf, myocardial infaretion (Ml), heart valve diseases and atrial septal ancurysm (ASA). The dependent variable was embolie heart disease while independent variables eneompassed socio--demographic factors, patients' history, and lifestyle. Data analym was carried out through SAS 9.3. ResuI1s: Tbe rate of embolie heart diseases (EHD) as etiology for isehemic stroke was 2 % (28/104). AF aecOUllted for 69% of embolic hean diseases and 22.8% of etiologies for isehemic strOke. Ischemie strokes prevalence was 3.5%, 2.5% and 1.2% rcspectlvely for heal't valve diseases, MI and ASA. The assoeialed factor was age (p = 0.000). Conclusion: The diagno is of a potential eardiae source of embolism is essential because of thewpeutic and prognostie implications. Wherefore, th is necd for cardiovascular examination particularly Holter ECG and cardiac u1trasound examination which are not always accessible to our populations.
Keywords: Stroke; Is<:hemia; Embolie heart disease; Benin